Rekayasa Ulang Lantai Produksi PT. X dengan Metode Systematic Layout Planning - Fadilah, Alif Radzaki; Winarno, Winarno (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
PT X is a company that can produce and engineer machine tools engaged as a manufacturer of agricultural, livestock, plantation, and fishery machine tools. The arrangement of the layout of the production facility from the work environment (production floor) greatly affects the production process activities to run well. The increase in productivity of the company is driven by every interested party in it. With the results of these improvements, it will certainly encourage the level of performance, productivity, and quality of the products produced with the minimum possible production costs expected by management. In-depth analysis and evaluation are needed to identify problems and potential improvements in the layout of the production floor. Systematic Layout Planning (SLP) is an approach used in order to optimize material moving costs and mileage to redesign a layout. After optimizing the layout, the results of the current layout have a cost or Material Handling Cost (OMH) of IDR 2,736,750 with a total mileage of 182,45 m. On the other hand, the proposed layout has a total mileage of 175,6 m, resulting in an OMH of IDR 2,634,000. This can prove that there was a decrease in total OMH of IDR 102,750 so that the proposed layout can be applied.